(untitled) (Journal of Mechanical Engineering, 2016)
Supply chain flexibility is a competitive measure of supply chain aspects. It is a linkage medium between supply chain players and business performance. It absorbs the change in market conditions, demand volume and mix, product differentiations, commodity prices, availability of technology, labor costs, and exchange rates, utilization of equipment, production and logistics environment, cultural issues or any disruption in supply chain elements. This conception can be used as flexible guide that develop very well for multistage supply chains and it is established a model to meet the balancing situation of supply chain flexibilities by adjusting weight and individual probabilities. These results would lead to support and accommodate the managerial decisions as well as global supply chain management strategy.